Glyphosate use and associations with non-Hodgkin lymphoma major histological sub-types: findings from the North American Pooled Project - Pahwa, Manisha; Beane Freeman, Laura E; Spinelli, John J; Blair, Aaron; McLaughlin, John R; Zahm, Shelia Hoar; Cantor, Kenneth P; Weisenburger, Dennis D; Punam Pahwa, Punam Pahwa; Dosman, James A; Demers, Paul A; Harris, Shelley A (Scandinavian Journal of Work, Environment & Health, 2019)
' ' OBJECTIVES ': 'Some epidemiological studies have suggested positive associations between glyphosate use and non-Hodgkin lymphoma (NHL), but evidence is inconsistent and few studies could evaluate histological sub-types. Here, associations between glyphosate use and NHL incidence overall and by histological sub-type were evaluated in a pooled analysis of case–control studies. ' ' METHODS ': 'The analysis included 1690 NHL cases [647 diffuse large B-cell lymphoma (DLBCL), 468 follicular lymphoma (FL), 171 small lymphocytic lymphoma (SLL), and 404 other sub-types] and 5131 controls. Logistic regression was used to estimate adjusted odds ratios (OR) and 95% confidence intervals (CI) for NHL overall and sub-types with self-reported ever/never, duration, frequency, and lifetime-days of glyphosate use. ' ' RESULTS ': 'Subjects who ever used glyphosate had an excess of NHL overall (OR 1.43, 95% CI 1.11–1.83). After adjustment for other pesticides, the OR for NHL overall with "ever use" was 1.13 (95% CI 0.84–1.51), with a statistically significant association for handling glyphosate >2 days/year (OR 1.73, 95% CI 1.02–2.94, P-trend=0.2). In pesticide-adjusted sub-type analyses, the ordinal measure of lifetime-days was statistically significant (P=0.03) for SLL, and associations were elevated, but not statistically significant, for ever years or days/year of use. Handling glyphosate >2 days/year had an excess of DLBCL (OR 2.14, 95% CI 1.07–4.28; P-trend=0.2). However, as with the other sub-types, consistent patterns of association across different metrics were not observed. ' ' CONCLUSIONS ': 'There was some limited evidence of an association between glyphosate use and NHL in this pooled analysis. Suggestive associations, especially for SLL, deserve additional attention.
Keywords: Canada; cancer; case–control study; glyphosate; histological sub-type; non-Hodgkin lymphoma; North American Pooled Project; pesticide; pooled study; USA